Classical economics and modern theory : studies in long-period analysis - Kurz, Heinz D.; Salvadori, Neri. (London ; New York : Routledge, 2003)
"The essays reprinted in the book contain original findings and new vistas on old problems and show the reader how the different parts hang together. As such the book will be of great interest to every scholar working within the field of economic theory and the history of economic thought."--BOOK JACKET
Includes bibliographical references and index.
oif 03/01/2014
Loans
Keywords: Neoclassical school of economics; Classical school of economics; Economic development